Effect of light emitted by diodes (LED) on cell viability - Farro-Tello, Jhon Elvis (2020)
Objetive: Identify the effect of concomitant use of four wavelengths; red, 645-700nm; blue, 439-440nm; yellow, 586 nm, and green 509-510nm, at 35.8mW and 62.81mW of light power over cell viability at 10, 20 and 30 minutes of exposure. Material and Methods: A lamp was designed using light emitting diodes, which had a microcontroller that allowed time and power control of the light energy emitted to the cells. Peripheral blood lymphocytes were separated using ficoll hypaque, then exposed to light for 10, 20 and 30 minutes and evaluating their viability by combining them with ethidium bromide and acridine orange at the end of each time for which an immunofluorescence microscope was used. Results: viability of the leukocytes after irradiation by the light emitting diode lamp at an electrical power of 1028.8 mW was 93%, 70% and 51% at 10, 20 and 30 minutes, respectively, while their respective controls had 93 %, 91% and 86%. The viability of the Leukocytes after their irradiation by the light emitting diode lamp at an electric power of 1681.3mW was 93%, 75% and 45% at 10, 20 and 30 minutes, respectively, while their respective controls had 94%, 91% and 86%. Conclusions: The exposure of the cells to the light emitted by diodes (LED), to the electric powers of 1028.8mW and 1681.3mW generate reduction of their viability after 10 minutes of irradiation compared to their respective controls.